Radiation protection in newer medical imaging techniques: CT colonography - International Atomic Energy Agency (International Atomic Energy Agency, 2014)
This publication has been developed by the IAEA in collaboration with the World Health Organization, the International Society of Radiology and the International Commission on Radiological Protection. It addresses issues associated with high patient doses received from multi-detector computed tomography (MDCT) in colonography and provides data on patient dose and risk levels, as well as information for practitioners on optimizing techniques.